ENVIRONMENTAL MANAGEMENT ACCOUNTING: THE CASE OF THE RUBBER TIRE MANUFACTURING COMPANY IN VIET NAM - Tran Thi Nga; Ho Thi Anh Dao, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
In the last decades, the concept of sustainable development has been a popular subject in academic researches and the business community. To be considered as a sustainable business, becoming an environmentally friendly organization is critical. Environmental management accounting is an important tool to help enterprises to reach this goal. However, the application of environmental management accounting in Vietnam is still low in comparison to its role. The paper uses a case-study method that chooses a tire manufacturing company in central Vietnam to identify environmental cost, apply material flow accounting cost, and build criteria for environmental performance evaluation. The suggestion for the improvement of environmental management accounting implementation in Vietnam is also discussed. This study hopes to contribute to the popularization of environmental management accounting in the Vietnam business community.